Insights from sentiment analysis to leverage local tourism business in restaurants - Yu, Ting (2021)
Yu, T., Rita, P., Moro, S., & Oliveira, C. (2021). Insights from sentiment analysis to leverage local tourism business in restaurants. International Journal of Culture, Tourism, and Hospitality Research. https://doi.org/10.1108/IJCTHR-02-2021-0037 --------------------------------------------- Funding Information: The work by S. Moro and C.Oliveira was partially funded by national funds through FCT ‐ Fundação para a Ciência e Tecnologia, I.P., under the project FCT UIDB/04466/2020. The work by P. Rita was partially funded by national funds through FCT ‐ Fundação para a Ciência e Tecnologia, I.P., under the project FCT UIDB/04152/2020 ‐ Centro de Investigação em Gestão de Informação (MagIC). Publisher Copyright: © 2021, Emerald Publishing Limited.